Copper(II) and Sodium(I) Complexes based on 3, 7‐Diacetyl‐1, 3, 7‐triaza‐5‐phosphabicyclo[3.3.1]nonane‐5‐oxide: Synthesis, Characterization, and Catalytic Activity. Issue 19 (31st August 2018) - Mahmoud, Abdallah G.; Guedes da Silva, M. Fátima C.; Śliwa, Ewelina I.; Smoleński, Piotr; Kuznetsov, Maxim L.; Pombeiro, Armando J. L.
Abstract: The reaction of 3, 7‐diacetyl‐1, 3, 7‐triaza‐5‐phosphabicyclo[3.3.1]nonane (DAPTA) with metal salts of Cu II or Na I /Ni II under mild conditions led to the oxidized phosphane derivative 3, 7‐diacetyl‐1, 3, 7‐triaza‐5‐phosphabicyclo[3.3.1]nonane‐5‐oxide (DAPTA=O) and to the first examples of metal complexes based on the DAPTA=O ligand, that is, [Cu II (μ‐CH3 COO)2 (κ O ‐DAPTA=O)]2 (1 ) and [Na(1κ OO′ ;2κ O ‐DAPTA=O)(MeOH)]2 (BPh4 )2 (2 ). The catalytic activity of1 was tested in the Henry reaction and for the aerobic 2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (TEMPO)‐mediated oxidation of benzyl alcohol. Compound 1 was also evaluated as a model system for the catechol oxidase enzyme by using 3, 5‐di‐ tert ‐butylcatechol as the substrate. The kinetic data fitted the Michaelis–Menten equation and enabled the obtainment of a rate constant for the catalytic reaction; this rate constant is among the highest obtained for this substrate with the use of dinuclear Cu II complexes. DFT calculations discarded a bridging mode binding type of the substrate and suggested a mixed‐valence Cu II /Cu I complex intermediate, in which the spin electron density is mostly concentrated at one of the Cu atoms and at the organic ligand. Abstract : PTA meeting : A Cu II dimer with a 3, 7‐diacetyl‐1, 3, 7‐triaza‐5‐phosphabicyclo[3.3.1]nonane‐5‐oxide (DAPTA=O) ligand is synthesized and fully characterized, and its catalytic activity is investigated, for example, as a model system for the catechol oxidase enzyme. The proposed mechanism considers a monodentate binding of the substrate, the formation of a mixed‐valence Cu II /Cu I species, and the cooperation of co‐ligands.